2022
DOI: 10.4018/jgim.315646
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quality of Big Data Marketing Analytics (BDMA) on the Market and Financial Performance

Abstract: Impact of quality of big data marketing analytics (BDMA) was analyzed, with special attention to the BDMA dimensions of technology and information quality, and the level of deployment on perceived market and financial performance. The sample was collected with Canadian and U.S. marketing respondents with experience in big data (BD) deployment (N=236). The model analysis was done with PLS-SEM. The study highlights how technology and information quality are related to the market and financial performance with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Dataset quality is one example of this. While Haverila et al (2022) reported that data quality was an important consideration in Afghanistan, Khan et al's (2012) study in Indonesia found that low-quality data did not affect engagement levels (Purwanto et al, 2018). The current study, however, is less concerned with how factors such as data quality affect user engagement.…”
Section: Promoting Continued Usementioning
confidence: 57%
See 1 more Smart Citation
“…Dataset quality is one example of this. While Haverila et al (2022) reported that data quality was an important consideration in Afghanistan, Khan et al's (2012) study in Indonesia found that low-quality data did not affect engagement levels (Purwanto et al, 2018). The current study, however, is less concerned with how factors such as data quality affect user engagement.…”
Section: Promoting Continued Usementioning
confidence: 57%
“…While the potential value of OGD has been made clear from previous studies, it is also clear that the realisation of this value is often limited by government involvement (Janssen et al, 2012;. This can and often does significantly affect the quality of data, as well how and how often data is used (Haverila et al, 2022;Liu et al, 2023). Recent research has emphasised the need to understand the factors at play in encouraging the public to use open data and has tried to identify measures that could effectively improve data use.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed et al(2022) proposed the impact of the quality of big data marketing analysis on market and financial performance, emphasizing how technology and information quality are related to market and financial performance, with high predictive power and strength [10].The application of big data plays an important role in the management of precision portrait marketing resources. This paper studies how to integrate cloud and edge computing resources, including data storage and transmission, allocation and scheduling of computing tasks.…”
Section: Research On the Integration Management Strategy Of Marketing...mentioning
confidence: 99%
“…Du & Shu (2022) focused on using Deep Learning and Bionic Algorithm to explore of financial market credit scoring and risk management. The results of in-depth research in this area include quality of big data marketing analytics (Haverila et al, 2022); financial risk early warning model (Li et al, 2022); intelligent employee retention system (Srivastava et al,2021); analyze the market risks of A+H shares by BPNN algorithm (Wu et al,2022).…”
Section: Literature Reviewmentioning
confidence: 99%